2022
DOI: 10.1007/s42832-022-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil legacy effects and plant—soil feedback contribution to secondary succession processes

Abstract: The PSF of three species is positive in response to different soil origin.• The PSF of early-species is negative in response to plant growth period.• The PSF of mid-and late-species is negative in early-species soil over time.• The PSF of mid-and late-species is neutral in mid-species soil over time.• The PSF of mid-and late-species is positive in late-species soil over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, the process of returning forest functions is time-consuming and requires a succession process. Qu et al (2023) argued that the process of succession in ex-mining ecosystems is challenging. This is because the accumulation of certain chemical elements inhibits the natural microbial community from producing enzymes that play an important role in the association between plant-soil feedback (PSF), which forms a community interaction in the local ecosystem.…”
Section: Implementation Of Coal Mine Reclamation In Indonesiamentioning
confidence: 99%
“…However, the process of returning forest functions is time-consuming and requires a succession process. Qu et al (2023) argued that the process of succession in ex-mining ecosystems is challenging. This is because the accumulation of certain chemical elements inhibits the natural microbial community from producing enzymes that play an important role in the association between plant-soil feedback (PSF), which forms a community interaction in the local ecosystem.…”
Section: Implementation Of Coal Mine Reclamation In Indonesiamentioning
confidence: 99%
“…Ecological studies in field settings frequently use fungicide to eliminate AMF, as opposed to inoculation (Koricheva et al, 2009). Although the methodological constraints of field inoculation are understandable, the ecological effects of fungicide are likely broader than those of inoculation, because fungicide wipes out a wide range of soil microbial mutualists as well as pathogens (Newsham et al, 1995;Schmidt et al, 2000;Qu et al, 2022). In a study of plant-soil feedback effects using 24 grassland species grown in conspecific or interspecific soils, Petermann et al (2008) found that the application of fungicide increased plant biomass in nearly every species, an effect they attributed to fungicides eliminating a broad swath of soil fungal pathogens, thereby increasing plant productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-soil feedbacks are major drivers of plant growth, long-term survival, and patterns of biodiversity in plant communities, that are especially important in an era of global change (van der Putten et al 2013, Van Nuland et al 2017, Semchenko et al 2022. Through unique alterations in the biological and chemical properties of soil due to plant traits and inputs that lead to changes to the microbial community composition and function, the conditioning effects of plant communities drive patterns of productivity, composition, and succession in future plant communities through soil legacy effects (Li et al 2023;Lu et al 2023;Qu et al 2023). Although plant-soil feedbacks can range from facilitative to inhibitory, microbially mediated legacy effects can persist in the soil for long periods of time after the conditioning plant species have disappeared (Kulmatiski & Beard 2011;Schmid et al 2021).…”
Section: Introductionmentioning
confidence: 99%